Unremitting chronic skin lesions: a case of delayed diagnosis of glucagonoma. Issue 5 (3rd September 2019) - Kawsar, Hameem I.; Habib, Alma; Saeed, Azhar; Saeed, Anwaar
ABSTRACT: A 54-year-old Caucasian male with history of hypertension, hyperlipidemia, insulin-dependent diabetes mellitus, and chronic skin rash of 4 years presented to the emergency department with worsening rash and weight loss. Physical examination revealed diffuse erythematous rash, skin ulceration, bullae with associated paresthesia in the lower extremities, trunk, bilateral upper extremities, and palms and soles. A computed tomography (CT) scan with contrast showed a large, heterogenously enhancing pancreatic mass measuring 9.4 × 3.8 cm with surrounding low-attenuation soft tissue thickening. Blood tests showed hemoglobin A1C of 10.0%. Glucagon level was elevated to 2, 178 (normal < 80 pg/dl). Endoscopic ultrasound (EUS)-guided fine needle aspiration (FNA) from the pancreatic mass was suggestive of pancreatic endocrine tumor. The tumor cells were positive for synaptophysin, chromogranin, CD56, and pan-cytokeratin with focal positivity for glucagon, suggestive of glucagonoma. The patient underwent distal pancreatectomy along with splenectomy and cholecystectomy. The glucagon level normalized to 25 pg/dl within a week of tumor resection, and during his 6-week outpatient follow up, skin rash had completely resolved.